Understanding history, historical thinking, and historical consciousness, in learning history: An ex post-facto correlation - Bunari Bunari; Muhammad Rijal Fadli; Asyrul Fikri; Johan Setiawan; Ardian Fahri; Ikfi Muallifa Izzati (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aims to analyze the relationship between historical understanding, historical thinking, towards historical consciousness in learning history. This type of research is ex post-facto with a correlational design. The population is class X high school students in Yogyakarta, with a sample of 177. The side technique uses cluster random sampling. Data collection uses instruments in the form of historical understanding tests, historical thinking tests, and historical consciousness questionnaires. Data analysis was carried out through partial correlation and multiple correlations with a significance level of 0.05, and the prerequisite test analysis used normality, linearity, and multicollinearity tests. The results show that the relationship between historical understanding, historical thinking, and historical consciousness in history learning has a strong and significant correlation. These three components should not be separated from the history learning process so that history learning is more meaningful for its historical values.